Enhancing climate-resilient livelihoods of women, youth and vulnerable populations in the Lake Victoria Zone Region of Kenya: A case of Homabay and Migori counties - Adam, Rahma; Amwata, Dorothy; Ndiema, Nicholas; Osa, Philip (WorldFish, 2023)
Climate change and variability plays a central role in the livelihoods of fishing communities along the Lake Victoria Zone Region of Kenya. Women and vulnerable populations are the worst hit; therefore, this study aims to identify the effects of changes in rainfall and temperature on the livelihoods of women, youth and other vulnerable populations in the Lake Victoria Region in Kenya that depend on the fish value chain, and to assess the coping and adaptation strategies to deal with climate and other environmental changes, taking Homabay and Migori counties as a case in point. A cross-sectional study design, incorporating mixed qualitative and quantitative methods, was adopted in this study. This study analyzed data from the 480 sample households, 42 key informant interviews (KIIs) and six focus group discussions (FGDs). The participants were drawn from the different fish valuechain players, namely boat makers and repairers, boat crew, fishermen, beach management unit, small- and large-scale fish traders, transporters, county fisheries departments, county meteorological departments, the Kenya Revenue Authority and cage farmers. Content analysis was used to analyze data from KIIs and FGDs. A spatial analysis integrating socioeconomic and spatial data was used to establish factors influencing the vulnerability of women, youth and people living with disabilities to impacts of climate change in the counties. Results show that there are distinct sexdisaggregated roles among the fisher communities, with females playing specifically boat managers, small traders and fish assemblers, while males were fishermen, boat makers and repairers.